Use of carbon fiber layers and steel plates to repair fatigue damage at the rib-to-rib butt-welded connections of orthotropic steel deck under fatigue loading - Shakir, Saifaldien (My University, 2020)
Orthotropic steel decks (OSDs) are one of the most chosen solutions when the dead-weight is the primary concern. Due to their light construction style and low rigidity fatigue have been observed as cracks running through especially in the connections because of concentrated and residual stresses at welded details. Studies concerning the cases which use (RR) butt-welded connections are limited in the literature. In this study, a set of cyclic loading experiments is carried out for the investigation of the fatigue life and crack propagation characteristics of full-scale rib-to-rib (RR) butt-welded connections with trapezoidal crosssections. Two repairment methods based on bonded carbon fiber reinforced polymer layers (CFRP) and bolted steel plates (BSP) for the failed specimens are utilized and fatigue life improvements are tested. The cyclic test rig is first verified under static loading with strain gage readings which are compared to finite element simulations. Crack growth characteristics are observed as provided by dye-penetrant and dynamic stiffness crack detection methods. Crack lengths against the number of cycles were recorded for construction of the fatigue strength (S-N) Curves as given in AASHTO (2007). The test revealed that as long as the bond quality of the CFRP layers the steel plates were maintained, the decrease in stress demand was enough to extend the fatigue life from AASHTO fatiguedesign Category E’ for the unrepaired configuration to the infinite fatigue life range. Test results also showed that the dynamic stiffness curve was drastically improved for the repaired specimens. To better understand the experimental results a numerical study based on finite element simulations is undertaken as well. The results indicate a remarkable decrease in stress levels in fatigue sensitive details after the application of proposed repair methods. Overall, the performance of these two lightweight methods for repairing movable OSD proved to be efficient and durable.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2020
Keywords: CFRP layers; Orthotropic steel deck; Bolted steel plates